Laboratorium Diagnosis of Clostridium difficile Infection - Grace Nerry Legoh; Rustadi Sosrosumihardjo (The Indonesian Society for Digestive Endoscopy, 2006)
Clostridium difficile is the most important cause of antibiotic associated diarrhea, and pseudomembranous colitis, a severe infection of the colon. Strain Clostridium difficile produce two potent toxin, toxin A (enterotoxin) and toxin B (cytotoxin). These two toxins are both responsible for the diarrhoea and inflammation seen in patients treated due to infection, especially the broad spectrum antibiotics. Direct detection of Clostridium difficile cytotoxin from faecal specimen using mammalian tissue culture lines is considered the standard diagnostics test of Clostridium difficile infection. This test is very sensitive but requires a minimum two days to complete. In order to improve the threshold of diagnosis and treatment, a number of enzyme immunoassay Methods have been used, with a reported sensitivity to either toxin A or toxin B. Keywords: Clostridium difficile, cytotoxin, diarrhea, enzyme immunoassay